Prevalence of smoking and incidence of initiation in the Latin American adult population: the PLATINO study - Valdivia Gonzalo; Jardim José R; Perez-Padilla Rogelio; Muiño Adriana; Hallal Pedro C; Lopez Maria V; Menezes Ana M; Pertuzé Julio; de Oca Maria M; Tálamo Carlos; Victora Cesar G (BMC, 2009)
Abstract Background The PLATINO project was launched in 2002 in order to study the prevalence of chronic obstructive pulmonary disease (COPD) in Latin America. Because smoking is the main risk factor for COPD, detailed data on it were obtained. The aim of this paper was to evaluate the prevalence of smoking and incidence of initiation among middle-aged and older adults (40 years or older). Special emphasis was given to the association between smoking and schooling. Methods PLATINO is a multicenter study comprising five cross-sectional population-based surveys of approximately 1,000 individuals per site in Sao Paulo (Brazil), Santiago (Chile), Mexico City (Mexico), Montevideo (Uruguay) and Caracas (Venezuela). The outcome variable was smoking status (never, former or current). Current smokers were those who reported to smoke within the previous 30 days. Former smokers were those who reported to quit smoking more than 30 days before the survey. Using information on year of birth and age of smoking onset and quitting, a retrospective cohort analysis was carried out. Smoking prevalence at each period was defined as the number of subjects who started to smoke during the period plus those who were already smokers at the beginning of the period, divided by the total number of subjects. Incidence of smoking initiation was calculated as the number of subjects who started to smoke during the period divided by the number of non-smokers at its beginning. The independent variables included were sex, age and schooling. Results Non-response rates ranged from 11.1% to 26.8%. The prevalence of smoking ranged from 23.9% (95%CI 21.3; 26.6) in Sao Paulo to 38.5% (95%CI 35.7; 41.2) in Santiago. Males and middle-aged adults were more likely to smoke in all sites. After adjustment for age, schooling was not associated with smoking. Using retrospective cohort analysis, it was possible to detect that the highest prevalence of smoking is found between 20-29 years, while the highest incidence is found between 10-19 years. Age of smoking onset tended to decline over time among females. Conclusion The prevalence of smoking varied considerably across sites, but was lower among countries with national anti-smoking campaigns.